(untitled) (Ustozlar uchun, 2026)
Thanks to creative software solutions for Raman and fluorescence analysis, modern laser technology is becoming more important in medicine and dentistry for the quick diagnosis and treatment of medical disorders. Broadband, high-energy laser radiation serves two purposes: first, as a therapeutic tool [1, 2, 3, 4]; and second, as a way to enhance a biological specimen’s Raman luminous diagnostic potential [5] (particularly in the context of biophotometry). In order to diagnose diseases and processes of microbial, metabolic, neoplastic, or other origins, the methodology uses recorded spectral characteristics from Raman and/or luminescence fluorescence diagnostics (RLFD) of the subjects under investigation (microbial metabolites, cells, tissues, and biological fluids in both healthy and pathological conditions) [6].